Inverted intercostal hernia of elastofibroma dorsi mimicking well-differentiated liposarcoma in the chest wall. (30th March 2022) - Yoshida, Rika; Yoshizako, Takeshi; Okamura, Kazuya; Ando, Shinji; Nakamura, Megumi; Ishikawa, Noriyoshi; Kitagaki, Hajime
Elastofibroma dorsi is a well-known benign chest wall tumor. Herein, we present a case in which an elastofibroma protruded into the thoracic cavity, leading to inverted intercostal hernia. Imaging revealed a soft tissue mass containing fat, typical of elastofibroma dorsi; however, precise diagnosis was difficult owing to the location of this mass that protruded into the thoracic cavity. Liposarcoma had to be ruled out because it was a growing fat-containing mass. Considering that the tumor moved while the patient was undergoing computed tomography-guided biopsy in the prone position, a diagnosis of inverted intercostal hernia of elastofibroma dorsi was made. We report this case with a review of current literature.